Gender Identities in Organized Sports—Athletes' Experiences and Organizational Strategies of Inclusion - Braumüller, Birgit; Menzel, Tobias; Hartmann-Tews, Ilse (Frontiers in Sociology, 2020)
In relation to conceptualizing sports, beliefs about sex binary and male hegemony are dominant. To match these assumptions and provide level playing fields, sport systems are based on sex-segregation. Thus, people who do not fit into or reject fitting into sex categories are hindered from participating in sports, particularly organized sports. Studies on social exclusion of gender-identity minorities in sports mainly adopt a qualitative approach and focus on Anglophone countries. This research is the first to provide a comprehensive picture of the experiences of LGBT+ athletes in organized sports settings in Europe and is based on a quantitative online survey (n=2282). The current paper draws special attention to differences between cisgender and non-cisgender athletes (including transgender men, transgender women, non-binary and non-identifying individuals). Besides athletes’ experiences, organizational strategies of inclusion, derived from qualitative interviews with stakeholders from sport systems in five European countries (Germany, Scotland, Austria, Italy, and Hungary) are examined. Theoretically anchored in Cunningham’s (2012) multilevel model for understanding the experiences of LGBT+ individuals and Meyer’s (2003) minority stress model, the paper aims to (1) analyze the assessment of transnegativity and (2) examine negative experiences (prevalence, forms, perpetrators) of LGBT+ athletes from organized sport contexts in Europe; and (3) discuss inclusive strategies in sports organizations in Europe. Data reveal that transnegativity is perceived as a major problem in European sports, and non-cisgender athletes are the most vulnerable group, suffering particularly from structural discrimination. The implementation of inclusive strategies for non-cisgender athletes is perceived as a complex and essential task, but the sports organizations in the five countries differ substantially in terms of the status of implementation.